2017
DOI: 10.1093/jme/tjx124
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fly Cleaning Behavior on Carriage of Escherichia coli and Pseudomonas aeruginosa

Abstract: Flies are known to be mechanical vectors of bacterial, viral, and parasitic diseases. Although flies are known to transmit disease, the effects of cleaning behavior have not been well studied. This study quantified the cleaning effectiveness and behavior of three fly species: Sarcophaga bullata, Musca domestica L., and Drosophila virilis. Flies were transferred to plates of Escherichia coli or Pseudomonas aeruginosa and allowed to walk on the bacteria for a total of 5 min. After the flies were contaminated, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Invertebrates such as worms, insects, and amoebas can be used as animal models [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118]. They provide the ability to readily use large numbers of subjects due to fast reproduction, ease of handling, and small size.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Invertebrates such as worms, insects, and amoebas can be used as animal models [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118]. They provide the ability to readily use large numbers of subjects due to fast reproduction, ease of handling, and small size.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Our preliminary data also show that flies are able to feed on ORFV (DNA)-positive ovine crusts, dispense the diet into their crop and regurgitate and defecate the viral genome; this suggests that their body surfaces may be contaminated by their infected excreta. Furthermore, ORFV-positive droplets eventually present on the tip of the fly proboscis may be spread by grooming, thus contaminating their legs and possibly their wings, such has been observed for a number of bacteria [24,25]. Evidence shows that grooming increases significantly in flies exposed to bacteria compared to flies not exposed; this suggests that fly cleaning could affect the mechanical transmission of disease bacteria [25] and that a fly's ability to remove pathogens should also be kept in mind in the spread of ORFV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus shorter contact times would be more impacted by contact of body parts on transfer bacteria from contaminated surfaces to flies and from flies to food. In one of the few short term studies done to date, Jacques et al (2017) found the cleaning behavior of house flies and fruit flies resulted in the mechanical transmission of E. E. coli recovered from uninoculated food E. coli recovered from flies + E. coli recovered from uninoculated food coli to sterile petri plates after 5 min exposure to inoculated plates. Gill et al (2016) reported that house flies transmitted Campylobacter jejuni primarily by contact rather than through the digestive system even after ingestion.…”
Section: Discussionmentioning
confidence: 99%